Japan's admission to the Arctic Council and commitment to the rights of its indigenous Ainu people. Issue 1 (2nd January 2016) - Hossain, Kamrul; Maruyama, Hiroshi
Abstract: In 2013, Japan, along with four other Asian countries, was admitted to the Arctic Council (AC) as an observer. Japan's admission to the AC is noteworthy because of the expansion of its interests in the Arctic region. Japan's admission, as with the other observers in the AC, has been met by its willingness to pay due respect to the core values the AC holds, including respect for the rights of the indigenous peoples of the region. In this way, Japan has essentially agreed to respecting indigenous rights as part of its Arctic engagement. Japan has its own indigenous peoples within its own territory to whom it is committed. The main question this article examines is how the rights of indigenous peoples, as permanent participants in the AC to which Japan has committed to pay due respect as part of its Arctic engagement, are compatible with Japan's commitment at the national level to protect the rights of its own indigenous peoples, especially the Ainu.